Exploratory findings of prescribing unlicensed and off-label medicines among children and neonates - Shakeel, Sadia; Iffat, Wajiha; Nesar, Shagufta; Zaidi, Hina; Jamshed, Shazia Qasim (Dovepress, 2020)
Objective: A cross-sectional study was carried out to evaluate the practice of unlicensed and off-label drug prescribing/dispensing in children and neonates by physicians and clinical pharmacists in the metropolitan city of Karachi. Methods: The study was conducted for the duration of 5 months – November 2018 to March 2019 – in different clinics and tertiary care hospitals of Karachi, Pakistan. Respondents were interviewed by our researchers using 30 items questionnaire. Descriptive statistics were used to evaluate the answers of respondents to survey items. Pearson correlation and independent sample t-test were employed to recognize the association between the responses of participants and independent variables. P values less than 0.05 were considered statistically significant. Results: A total of 421 questionnaires were completed by physicians and clinical pharmacists. The mean age of the study participants was 49.5 years. Around 98% of pharmacists and 93.5% of physicians were well conversant with the definition of unlicensed and off-label drugs. Around 68% of physicians and 77% of pharmacists reported that they were more concerned about the efficacy of such drugs as compared to that of licensed medicines in children. The most frequent off-label categories observed in the study were dose (65.21%) and indication (17.52%). A vast majority (>80%) thought that approving new drugs by regulatory authorities will drop the occurrence of medication errors due to incorrect dosing. The British National Formulary (BNF) for children was used as the best reliable source of information among respondents. Conclusion: The present study highlighted the common practice of unlicensed and off-label drug prescribing in pediatrics; however, respondents showed their concern towards decreasing such practice and are likely to welcome initiatives intended to assure medication safety in children.